Evaluation of interdisciplinary treatment outcomes in patients with complete palate clefts Part 2. Quality of life and associated variables - Zdun-Ryżewska, Agata; Racka-Pilszak, Bogna; Wojtaszek-Słomińska, Anna; Basiński, Krzysztof; Majkowicz, Mikołaj; Banaszkiewicz, Agnieszka (Forum Ortodontyczne / Orthodontic Forum, 2019)
Measurement of the quality of life is necessary to properly evaluate the efficacy of treatment of patients with complete palate clefts, and also to plan the most effective interdisciplinary treatment. Assessments performed by specialists and patients alone as well as their family members may vary significantly. Aim. The aim of the research was to find variables (medical, psychological and social) related to the quality of life in patients with clefts who are about to finish treatment. Material and methods. The studies tookplace at the Outpatient Clinic of Orthodontics, University Dental Centre, Medical University of Gdańsk. The study included 45 patients with two types of clefts: bilateral cleft lip and palate (BCLP) and unilateral cleft lip and palate (UCLP). Psychological tools (Cantril Ladder and HADS) and the Questionnaire Survey of Attitudes and Concerns of Patients with Cleft Lip and Palate were used. Results. The greater the satisfaction with surgical treatment of the nose and upper lip, general satisfaction with one’s facial appearance (appearance, profile, lips, nose) and the better quality of speech – the higher the quality of life is. Satisfaction with chewing skills is also important for the quality of life. Lower quality of life in the present is associated with anxiety and depressive symptoms. Being bullied by others, effects of a cleft on the ability to make friends, meet partners and on self-confidence, and predicting the effects of a cleft on further learning are all significant. Conclusions. The quality of life of patients with clefts who finish treatment seems to be linked to many different factors: medical, psychological and social. Practical assistance provided to patients should include all these areas if we want to obtain not only good treatment outcomes but also better quality of life. (Zdun-Ryżewska A, Racka-Pilszak B, Wojtaszek-Słomińska A, Basiński K, Majkowicz M, Banaszkiewicz A. Evaluation of interdisciplinary treatment outcomes in patients with complete palate clefts. Part 2. Quality of life and associated variables. Orthod Forum 2019; 15: 5-13).